Исследование конструкционных характеристик срезов на дорне при производстве полых заготовок из цветных сплавов - Хорошилов, Олег Николаевич; Пономаренко, Ольга Ивановна (Белорусский национальный технический университет, 2006)
The calculation methods of the contact square between slug and mandrel with cuts and mandrel construction with cuts are given.
Investigation of constructional characteristics of cuts on mandrel at production of hollow slugs of non-ferrous alloys
Keywords: поперечное сечение; сплавы медные; трубы; площадь контакта; литье; кристаллизатор